Vocal biomarkers in heart failure—design, rationale and baseline characteristics of the AHF-Voice study - Kerwagen, Fabian; Bauser, Maximilian; Baur, Magdalena; Kraus, Fabian; Morbach, Caroline; Pryss, Rüdiger; Rak, Kristen; Frantz, Stefan; Weber, Michael; Hoxha, Julia; Störk, Stefan (Frontiers in Digital Health, 2025)
Acute heart failure (AHF) is a life-threatening condition and a common cause of hospitalization. The defining clinical feature of AHF is volume overload, leading to pulmonary and peripheral edema and consequently to weight gain. Vocal biomarkers have the potential to facilitate the early detection of worsening HF and the prevention of AHF episodes by offering a non-invasive, low-barrier monitoring tool. The AHF-Voice study is a prospective monocentric cohort study designed to investigate the trajectories of voice alterations during and after episodes of AHF, identify potential vocal biomarkers, and enhance the understanding of the pathophysiological mechanisms underlying these voice changes. It will examine the characteristics and determinants of vocal biomarkers, analyzing their correlations with patients' clinical status and comparing them to alternative clinical parameters in HF. Further, it aims to determine whether specific vocal biomarkers can accurately map different HF phenotypes and assess their association with patient trajectories. The study phenotypes patients hospitalized for AHF at admission and discharge, and follows them for a period of 6 months. During hospitalization, daily voice recordings are collected using a specially-designed smartphone app. Following discharge, patients are requested to continue daily voice recordings with their own smartphone for the subsequent six months the 6-month follow-up. Patient-reported outcome measures and body composition are assessed in the hospital and at follow-up visits. Sub-studies explore vocal fold oscillation through video-laryngostroboscopy and assess the feasibility of combining voice analysis with in-ear sensor technology for comprehensive digital phenotyping. A total of 131 patients were enrolled between April 2023 and November 2024: their mean age was 75 years (SD 10), 31% were women, 86% were in NYHA functional class III or IV, and 38% presented with de novo heart failure. Additionally, 59% of participants owned smartphones. The AHF-Voice study will provide insights into the potential of vocal biomarkers as reliable indicators of congestion, paving the way for innovative and accessible tools to support heart failure management.